Infiltration of Cellular Silicon by Molten Magnesium Alloys1 . Issue 10 (23rd March 2017) - Matz, Alexander Martin; Mocker, Bettina Stefanie; Heimann, Johann; Jost, Norbert
Abstract : Open‐pore cellular Si structures are manufactured by investment casting and, subsequently, infiltrated with molten Mg(‐Sn), representing the initial state for a formation of the intermetallic compound Mg2 Si1– x Sn x . The processing parameters which govern the evolution of microstructure after the infiltration process are studied in the alloy systems Mg‐Si and Mg‐Si‐Sn. The resulting microstructures are analyzed using SEM and EDS. It is found that an initial diffusion layer is already formed after infiltration. Its thickness can slightly be increased by raising the infiltration temperature of the Mg(‐Sn) melt. A variation in mold temperature does not show a noticeable impact. The comparison of the diffusion layer formed in the systems Mg‐Si and Mg‐Si‐Sn showed that a lower Sn content resulted in thicker layers. Abstract : In this study, intermetallic compounds on the example of Mg2 Si1–x Snx are fabricated by investment casting of open‐pore cellular Si structures and by, subsequently, infiltrating it with molten Mg alloys. The influence of processing parameters and of Sn content on the microstructural evolution is investigated and the initial state for a formation of the intermetallic compound is quantified by respect of the diffusion layer.